Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


12(x+3) -12(3x+1)=12(2x-4)  -------(1) divide this equn by 12 .then its equal to( x+3)-(3x+1)=(2x-4  )          x+3 -3x-1 =2x-4       ie x-3x+3-1 =2x-4   its same as-2x+2=2x-4         -taking 2x from RHS toLHS THEN   -2x-2x=-4-2==-4x=-6  orx=-6/-4=3/2=1.5
0 0 0
12x+36-36x-12=24x-48, -36x+36=12x-36, -36x+36=12x-36, -48x=-72, 48x=72, X=8÷12, X=4÷3
0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts